Bentuk Ketidakadilan dan Resistensi Tokoh Utama Perempuan dalam Kumpulan Cerkak Wit Tanjung Ngiringan Omah karya Bu Ageng Cicit - Raihana Nurani; Rahma Ari Widihastuti; Dhoni Zustiyantoro (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This study analyzes forms of injustice and resistance experienced by the female main character in the short story collection Wit Tanjung Ngiringan Omah using a feminist approach and James C. Scott's theory of resistance. Data collection involved reading and note-taking, with the reading process conducted heuristically and subsequently analyzed hermeneutically to achieve a deeper understanding. The research data consist of phrases and sentences related to forms of injustice, betrayal, and manifestations of resistance by the female protagonists, drawn from the short story collection Wit Tanjung Ngiringan Omah. The results indicate the presence of betrayal in the realms of romance, politics, economics, legitimacy, and protective functions. The female main character's resistance manifests in the form of open resistance (public transcript) and hidden resistance (hidden transcript), with hidden resistance being the most dominant form. Overall, this study demonstrates that power is not always manifested through physical rebellion but also through covert resistance.